2021
DOI: 10.2337/dc20-1836
|View full text |Cite
|
Sign up to set email alerts
|

Islet Autoimmunity and HLA Markers of Presymptomatic and Clinical Type 1 Diabetes: Joint Analyses of Prospective Cohort Studies in Finland, Germany, Sweden, and the U.S.

Abstract: To combine prospective cohort studies, by including HLA harmonization, and estimate risk of islet autoimmunity and progression to clinical diabetes. RESEARCH DESIGN AND METHODSFor prospective cohorts in Finland, Germany, Sweden, and the U.S., 24,662 children at increased genetic risk for development of islet autoantibodies and type 1 diabetes have been followed. Following harmonization, the outcomes were analyzed in 16,709 infants-toddlers enrolled by age 2.5 years. RESULTSIn the infant-toddler cohort, 1,413 (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…En conclusión, el número de autoanticuerpos de los islotes en el momento de la seroconversión predice de manera fiable el riesgo de tener diabetes tipo 1 a los 15 años. En los niños que conservan un solo autoanticuerpo, los genotipos HLA-DR-DQ pueden afinar aún más el riesgo de progresión (73) .…”
Section: El Futuro Cercanounclassified
“…En conclusión, el número de autoanticuerpos de los islotes en el momento de la seroconversión predice de manera fiable el riesgo de tener diabetes tipo 1 a los 15 años. En los niños que conservan un solo autoanticuerpo, los genotipos HLA-DR-DQ pueden afinar aún más el riesgo de progresión (73) .…”
Section: El Futuro Cercanounclassified
“…In our previous work [ 17 ], we harmonised IAb levels from our large, prospective Type 1 Diabetes Intelligence (T1DI) study cohort [ 18 ], identified the IAb type-specific titre thresholds (measured at the time of confirmed positivity) that maximised discrimination of 5-year type 1 diabetes risk, and used the thresholds to risk-stratify children in various age groups via survival analysis. This prior work demonstrated that IAb levels were useful in predicting type 1 diabetes onset, and motivated us to perform a more comprehensive assessment of the utility of measurement of IAb levels.…”
Section: Introductionmentioning
confidence: 99%
“…When multiple autoantibodies against islet-derived peptides are observed in childhood, at least 70% of children progress to clinical diabetes within 10 years through identifiable disease stages, including stage 1 (multiple islet autoantibodies and normoglycemia in an oral glucosetolerance test [OGTT]), stage 2 (multiple islet autoantibodies and dysglycemia in an OGTT) and stage 3 (clinical type 1 diabetes fulfilling WHO and ADA criteria). [2][3][4][5][6] However, stage 3 type 1 diabetes includes a very heterogenous group of people from an early-diagnosed asymptomatic hyperglycaemia observed in an OGTT to late-diagnosed severe ketoacidosis. Thus, careful definition of eligibility criteria according to the two presymptomatic stages of type 1 diabetes, and strict criteria within stage 3, can identify homogeneous study groups.…”
Section: Introductionmentioning
confidence: 99%
“…T A B L E 1 Primary and secondary end points of three type 1 diabetes prevention trials testing incretin-based therapy in islet autoantibody positive participants F I G U R E 1 Overview of the design and recruitment for three parallel type 1 diabetes prevention trials testing incretin-based therapy in islet autoantibody positive participants at various stages of type 1 diabetes. 1 See ref [5,6]; 2 See ref [4]; 3 Primary endpoint assessed before and at the end of intervention; 4 IAA (insulin autoantibody), GADA (glutamic acid decarboxylase antibody), IA-2A (insulinoma-associated protein 2 antibody), ZnT8A (zinc transporter 8 antibody). The majority of the islet autoantibody multipositive participants are recruited from The Finnish Type 1 Diabetes Prediction and Prevention (DIPP) Study, a populationrepresentative birth cohort study ongoing in three university hospitals in Finland.…”
Section: Introductionmentioning
confidence: 99%